Facts About Energy Drinks - Erica Bub; Karla Shelnutt (EDIS)
You can’t walk into a supermarket these days without seeing a wide selection of energy drinks, many claiming that they do everything from boosting your energy to helping you focus. In fact, energy drinks are so popular that, on average, Americans drank about 15 cups per person in 2007. But what’s in a typical energy drink? Do they really work? And are there any health risks from consuming them? This 4-page fact sheet was written by Erica Bub and Karla Shelnutt, and published by the UF Department of Family, Youth and Community Sciences, April 2012.